Hybrid Insulin Peptides Are Recognized by Human T Cells in the Context of DRB104:01 - Arribas-Layton, David; Guyer, Perrin; Delong, Thomas; Dang, Mylinh; Chow, I-Ting; Speake, Cate; Greenbaum, Carla J.; Kwok, William W.; Baker, Rocky L.; Haskins, Kathryn; James, Eddie A. (Diabetes (New York, N.Y.), 2020)
T cells isolated from the pancreatic infiltrates of nonobese diabetic mice have been shown to recognize epitopes formed by the covalent cross-linking of proinsulin and secretory granule peptides. Formation of such hybrid insulin peptides (HIPs) was confirmed through mass spectrometry, and responses to HIPs were observed among the islet-infiltrating T cells of pancreatic organ donors and in the peripheral blood of individuals with type 1 diabetes (T1D). However, questions remain about the prevalence of HIP-specific T cells in humans, the sequences they recognize, and their role in disease. We identified six novel HIPs that are recognized in the context of DRB1*04:01, discovered by using a library of theoretical HIP sequences derived from insulin fragments covalently linked to one another or to fragments of secretory granule proteins or other islet-derived proteins. We demonstrate that T cells that recognize these HIPs are detectable in the peripheral blood of subjects with T1D and exhibit an effector memory phenotype. HIP-reactive T-cell clones produced Th1-associated cytokines and proliferated in response to human islet preparations. These results support the relevance of HIPs in human disease, further establishing a novel posttranslational modification that may contribute to the loss of peripheral tolerance in T1D.